About our country-South Africa,The flag - Barnes L.; Awareness Publishing Group (Pty) Ltd (Gallo Manor: Awareness Publishing Group (Pty) Ltd, 2010)
A basic introduction to South Africa's national flag,including a description of the flag,rules governing use of the flag and instructions for drawing the flag.
Junior Non-Fiction-:Juvenile